Pengkajian Penerapan Teknik Budidaya Rhizophora mucronata dengan Stek Hipokotil - Mulyani, Neni; Kusmana, Cecep; Supriyanto (Jurnal Manajemen Hutan Tropika, 1999)
Research on the vegetative propagation of Rhizophora mucronata using hypocotyl cutting sistem was carried out at Faculty of Forestry, Bogor Agricultural University. Histological analysis of adventitous shoot was done at Biotechnology and Tree Breeding Laboratory, SEAMEO-BIOTROP. Three types of hypocotyl cutting (complete hypocotyl, top part of cut-hypocotyl and bottom part of cut-hypocotyl) were induced using 6-BAP hormones at 0 and 500 ppm. Adventitous shoot of bottom part of cut-hypocotyl appeared 140 days after planting. Shoot from complete hypocotyl and top part of cut-hypocotyl grew earlier than adventitous shoot from bottom part of cut-hypocotyl. Hystologycal analysis of adventitous shoot showed the existance of primary meristem, stipule and leaf primordia. The growth of complete hipocotyl was higher than both of top part of cut-hypocotyl and bottom part of cut-hypocotyl. There was no effect of hormone induction on the shoot growth of them.